Highly Enantioselective Synthesis of α-Amino Acid Derivatives by an NHC-Catalyzed Intermolecular Stetter Reaction - Jousseaume, Thierry; Wurz, Nathalie E.; Glorius, Frank (Angewandte Chemie International Edition, 2011)
PROTONtype: An NHC‐catalyzed (NHC=N‐heterocyclic carbene), highly asymmetric intermolecular Stetter reaction allows the atom‐economic and efficient formation of valuable α‐amino acid derivatives (see scheme); the key step is an intramolecular stereoselective protonation. For the first time, a β‐unsubstituted Michael acceptor was employed successfully in this kind of reaction, most importantly, with a broad range of different aldehydes.